(untitled) (Revista LIDER, 2020)
This paper analyses rural tourism as a form of promoting local development through direct commercialization of local food products along the Gastronomic Tourist Route of Santa Maria – Silveira Martins, Estado do Rio Grande do Sul, Brasil. The study is based on qualitative and quantitative/descriptive methods, and which data was recollected through directly through the application of 14 semistructured interviews and questionnaires applied to those who were responsible for the tourist establishments. The results obtained reveal that tourist activity and the commercialization of products on the route brings several benefits to a portion of the population directly involved with the activity, as well as to those who are indirectly involved. The results permit us to conclude that the development of tourism in this location requires greater specialization, needs extensive planning, investment in infrastructure and in human resources, in the quality of the commercialized products and also a greater involvement of the local population.